Carbon fiber dispersion and method for producing carbon paper

A copolymer-based method for dispersing carbon fibers in aqueous systems addresses the challenge of uniform dispersion, resulting in improved mechanical properties and stability of carbon paper.

JP7610653B2Active Publication Date: 2025-01-08HANSOL CHEM
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023106960
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-07-04
Filing Date
2023-06-29
Publication Date
2025-01-08
Estimated Expiration
2043-06-29

AI Technical Summary

Technical Problem

Existing methods struggle to uniformly disperse carbon fibers of certain lengths in aqueous systems, leading to agglomeration and reduced mechanical properties in carbon paper, particularly with longer fibers.

Method used

A method involving the use of a copolymer solution containing acrylic acid and acrylamide monomer units to hydrophilize carbon fibers, combined with a wetting agent and controlled stirring, results in a carbon fiber dispersion with improved dispersibility and stability, followed by molding and drying to produce carbon paper.

Benefits of technology

The method effectively disperses long carbon fibers, enhancing the mechanical properties of carbon paper by improving dispersibility and tensile strength, while maintaining stability against re-aggregation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610653000004
    Figure 0007610653000004
  • Figure 0007610653000005
    Figure 0007610653000005
  • Figure 0007610653000001
    Figure 0007610653000001
Patent Text Reader

Abstract

To provide a method of manufacturing a carbon fiber dispersion, aimed at improving both the dispersion stability of carbon fibers and the performance (such as tensile strength) of carbon paper, a method of manufacturing carbon paper, and a carbon fiber dispersion manufactured by the same.SOLUTION: A method of manufacturing a carbon fiber dispersion includes a first step of preparing a solution containing hydrophilic carbon fibers by adding carbon fibers and a wetting agent to a solvent, followed by stirring, and a second step of dispersing the hydrophilic carbon fibers by adding a copolymer solution to the solution containing the hydrophilic carbon fibers. The copolymer includes acrylic acid-based monomer units and acrylamide-based monomer units.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a carbon fiber dispersion and carbon paper, and to a carbon fiber dispersion and carbon paper produced thereby, which can increase the dispersion stability of carbon fibers and improve the performance (e.g., tensile strength) of the carbon paper. [Background technology]

[0002] Fiber-reinforced composite materials are made using fibers such as glass fiber, carbon fiber, aramid fiber, and silicon carbide fiber as reinforcing materials. Among these, carbon fiber-reinforced composite materials (CFRP) using carbon fiber have excellent physical properties such as a specific strength six times that of steel and a specific elastic modulus three times that of steel. As such, they are lightweight yet highly strong, and are widely used in aircraft and wind turbine rotors.

[0003] In addition, with the recent emergence of environmental issues, there has been an increase in research into recovering and reusing carbon fibers from carbon fiber reinforced composite materials that are discarded after use, and the related market is also expanding in size.

[0004] Methods for manufacturing carbon fiber reinforced composite materials using such carbon fibers and recycled carbon fibers include a method of mixing fibers in a woven, nonwoven, or short fiber state with resin to produce a composite material, and in order to produce a high-strength product, a nonwoven fabric must be produced to produce the composite material.

[0005] When fibers are manufactured into nonwoven fabric, their physical properties vary depending on the fiber thickness, length, arrangement, molding method, etc. There are pros and cons to molding methods that arrange the fibers in a uniform direction and molding methods that distribute them randomly, but the method of dispersing the fibers randomly has advantages over the molding method of arranging the fibers in a uniform direction, not only in terms of facility costs and operability, but also in terms of energy savings and environmental friendliness. However, randomly arranged fibers have the disadvantage that they can reduce the mechanical properties of the nonwoven fabric due to phenomena such as aggregation and twisting. In particular, such a decrease in physical properties occurs when the fibers are long, as they are bundled together in water due to the bonding forces between the fibers, making them less dispersible. Therefore, research is needed to uniformly disperse long fibers in order to improve the physical properties of nonwoven fabrics.

[0006] However, currently, the dispersants used to disperse existing carbon fibers, such as cellulose-based polymers such as CMC, are unable to uniformly disperse carbon fibers longer than a certain length.

[0007] Therefore, there is a demand for a method that can uniformly disperse carbon fibers of a certain length or more without deteriorating performance. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Republic of Korea Patent Publication No. 10-2022-0055337 Summary of the Invention [Problem to be solved by the invention]

[0009] Therefore, an object of the present invention is to provide a carbon fiber dispersion that effectively disperses carbon fibers in an aqueous system, a method for producing carbon paper, and a carbon fiber dispersion with excellent dispersibility and carbon paper with excellent properties produced thereby.

[0010] In particular, the object is to improve the mechanical properties of carbon paper by dispersing relatively long carbon fibers having an average length of 12 mm to 25 mm in an aqueous system.

[0011] However, the problems to be solved by the present application are not limited to those mentioned above, and other problems not mentioned will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]

[0012] According to one aspect of the present invention, a method for producing a hydrophilized carbon fiber solution includes the steps of: (1) adding carbon fiber and a wetting agent to a solvent and stirring the mixture; A second step of dispersing the hydrophilized carbon fibers by adding a copolymer solution to the solution containing the hydrophilized carbon fibers, The copolymer comprises an acrylic acid monomer unit and and an acrylamide-based monomer unit, A method for producing a carbon fiber dispersion is provided.

[0013] Another aspect of the present application is a carbon fiber dispersion produced by the method for producing the carbon fiber dispersion, pH is 2 or more and 12 or less, The viscosity is 10cp or more and 200cp or less. A carbon fiber dispersion is provided.

[0014] Yet another aspect of the present application is a method for producing a carbon fiber dispersion comprising the steps of: forming a carbon fiber dispersion produced by the method for producing a carbon fiber dispersion; A fourth step of drying the formed carbon fiber dispersion. A method for producing carbon paper is provided. Effect of the Invention

[0015] The method for producing a carbon fiber dispersion and the method for producing carbon paper according to the present invention have the effect of effectively dispersing carbon fibers (especially long fibers) in an aqueous system, thereby producing a carbon fiber dispersion with excellent dispersion stability and carbon paper with excellent properties.

[0016] In particular, by efficiently dispersing relatively long carbon fibers in an aqueous solution, the mechanical properties of the carbon paper can be improved. [Brief description of the drawings]

[0017] [Figure 1] 1 is a photograph showing a carbon fiber dispersion in which rope-like aggregates are formed. [Diagram 2] This is a photograph showing the dispersion of carbon fibers in carbon paper based on measurements taken using a 2D lab formation sensor device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The functions and effects of the present invention will be described in more detail below through specific examples of the present invention, however, these examples are merely presented as examples of the present invention and do not define the scope of the invention.

[0019] Prior to this, the terms and words used in this specification and claims should not be interpreted limited to their ordinary or dictionary meanings, but should be interpreted with a meaning and concept that corresponds to the technical idea of ​​the present invention, in accordance with the principle that an inventor can appropriately define the concept of a term in order to explain his / her invention in the best possible way.

[0020] Therefore, it should be understood that the configuration of the embodiment described in this specification is merely one of the most preferred embodiments of the present invention and does not fully represent the technical ideas of the present invention, and that there may be various equivalents and modifications that can replace them at the time of this application.

[0021] In this specification, the singular expression includes the plural expression unless the context clearly indicates otherwise. It should be understood that in this specification, the terms "comprise", "comprise", "have" and the like are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, and do not preclude the possibility of the presence or addition of one or more other features, numbers, steps, components, or combinations thereof.

[0022] In this specification, in the expressions "a to b" and "a~b" which indicate numerical ranges, "to" and "~" are defined as ≧a and ≦b.

[0023] A method for preparing a carbon fiber dispersion according to one aspect of the present application may include a first step of preparing a solution containing hydrophilized carbon fibers by adding carbon fibers and a wetting agent to a solvent and stirring the mixture, and a second step of adding a copolymer solution to the solution containing the hydrophilized carbon fibers to disperse the hydrophilized carbon fibers.

[0024] The copolymer may include an acrylic acid-based monomer unit and an acrylamide-based monomer unit.

[0025] The solvent may be water.

[0026] The copolymers may be random or block copolymers depending on the synthesis process.

[0027] The first step of the method for producing a carbon fiber dispersion of the present application may be a step of introducing hydrophilic groups capable of forming hydrogen bonds with water onto the hydrophobic surface of the carbon fiber to enable dispersion in water.

[0028] In addition, the second step is a step for inducing dispersion of the carbon fibers by electrostatic repulsion and preventing re-agglomeration of the carbon fibers by utilizing steric hindrance, and the copolymer solution in which the copolymer is dissolved in a solvent may be mixed with the carbon fibers that have been appropriately hydrophilized in the first step, and a certain amount of solvent may be added to allow proper dispersion.

[0029] For example, in the second step, the solution containing the hydrophilized carbon fibers prepared in the first step (which may contain carbon fibers, a solvent, a wetting agent, a binder, etc.) can be mixed with the copolymer solution (a copolymer (dispersant) and a solvent in which the copolymer has been diluted (e.g., water)) in an amount 1 to 50 times the weight of the carbon fibers.

[0030] Meanwhile, the carbon fiber can be selected from PAN-based, Pitch-based, Cellulose-based, recycled carbon fiber reused as prepreg by chemical / physical methods, or a combination thereof.

[0031] In one embodiment, in the first step, a binder (binder fiber or binder polymer) may be additionally added.

[0032] The binder fiber or binder polymer is used to increase the binding strength of the carbon paper after the drying step during the manufacture of the carbon paper, and may be, for example, polyvinyl alcohol (PVA) fiber, low-melting-point polyester (LMPET), polyvinyl alcohol resin, etc.

[0033] In one embodiment, the first step can be performed by applying a shear force at a speed of 500 to 2,000 rpm to minimize damage to the fibers contained in the carbon fiber dispersion, and a device capable of applying a high shear force, such as a pulper, an overhead stirrer, or a knife beater, can be used.

[0034] In one embodiment, the hydrophilized carbon fibers can be dispersed by stirring at a speed of 1,000 rpm or less in the second step.

[0035] The stirring speed may be, for example, 1,000 rpm or less, 800 rpm or less, 500 rpm or less, or 300 rpm or less.

[0036] At this time, an impeller designed to minimize vortex generation is used to stir the mixture, dispersing and stabilizing the carbon fibers.

[0037] In one embodiment, the carbon fibers may have an average length of 5 mm or more. For example, the carbon fibers may have an average length of 6 mm or more, 10 mm or more, 12 mm or more, 15 mm or more, or 20 mm or more.

[0038] In one embodiment, the wetting agent may be a cationic surfactant, an anionic surfactant, a non-ionic surfactant, or a combination thereof.

[0039] For example, the wetting agent may be an EO (ethylene oxide) / PO (propylene oxide) copolymer surfactant, a PEO (polyethylene oxide)-based surfactant, a PEG (polyethylene glycol)-based surfactant, or a combination thereof.

[0040] In one embodiment, the carbon fiber dispersion may contain 0.1 wt % or more and 10 wt % or less of the copolymer and 0.01 wt % or more and 10 wt % or less of the carbon fiber, based on a total content of 100 wt % of the carbon fiber dispersion.

[0041] If the content of the copolymer exceeds the above range, the viscosity of the dispersion increases, making it difficult to dehydrate and dry the carbon paper during preparation, whereas if the content is below the above range, the dispersion of the fibers may be poor.

[0042] An appropriate content of the carbon fibers can be selected according to the target basis weight when preparing the web. If the content of the carbon fibers is above or below the range, damage due to friction increases or wetting is not performed properly.

[0043] In one embodiment, the binder (binder fiber) may be contained in an amount of 0.001% by weight or more and 5% by weight or less, based on a total content of the carbon fiber dispersion of 100% by weight.

[0044] If the content of the binder fiber is below the above range, suitable strength cannot be obtained.

[0045] In addition, the carbon fiber dispersion may contain the wetting agent in an amount of 0.01% by weight or more and 5% by weight or less, based on a total content of 100% by weight of the carbon fiber dispersion.

[0046] In one embodiment, the molar ratio of the acrylic acid-based monomer units to the acrylamide-based monomer units (mol % of the acrylic acid-based monomer units:mol % of the acrylamide-based monomer units) may be 10:90 to 90:10, based on 100 mol % of the total content of the copolymer.

[0047] For example, the molar ratio of the acrylic acid monomer units to the acrylamide monomer units may be 90:10, 80:20, 70:30, 60:40, 50:50, 40:60, 30:70, 20:80, 10:90, or may be 30:70 to 70:30.

[0048] When a homopolymer in which acrylic acid or acrylamide is polymerized alone is used as a dispersant, the carbon fibers cannot be dispersed properly.

[0049] In one embodiment, the monomer polymerized as the acrylic acid-based monomer unit of the copolymer may be acrylic acid, methacrylic acid, itaconic acid, 2-acrylamido-2-methylpropane sulfonic acid, maleic acid, or a combination thereof.

[0050] In addition, the monomer polymerized as the acrylamide-based monomer unit of the copolymer may be acrylamide, methacrylamide, or a combination thereof.

[0051] The copolymer may have a pH of 5 or more and 10 or less, and a viscosity of 100 cp or more and 20,000 cp or less.

[0052] For example, the pH of the copolymer may be from 5 to 9. If the pH of the carbon fiber dispersion is above or below this range, the dispersant may deteriorate over time, and the dispersion performance of the carbon fibers may decrease.

[0053] The copolymer may be provided with an alkali metal, alkaline earth metal, amine compound, or a combination thereof to adjust the pH of the copolymer.

[0054] In particular, the amine compound may be an amine compound having a pH of 9 or higher.

[0055] For example, sodium hydroxide, potassium hydroxide, ammonium hydroxide, lithium hydroxide, dimethylamine, trimethylamine, monoethanolamine, diethanolamine, triethanolamine, arginine, tromethamine, diisopropanolamine, triiospropanolamine, etc. can be used to adjust the pH of the copolymer, but are not limited to these.

[0056] In addition, if the viscosity of the copolymer exceeds the above range, the viscosity becomes too high, which is disadvantageous for use, whereas if the viscosity is below the above range, the carbon fibers cannot be dispersed properly.

[0057] On the other hand, the weight average molecular weight of the copolymer may be 100,000 or more and 5,000,000 or less.

[0058] If the molecular weight of the copolymer exceeds the above range, the viscosity becomes high, which is disadvantageous for use, and if it is below the range, the dispersion of the carbon fibers is not performed properly.

[0059] In addition, depending on the molecular weight range, a copolymer having a low molecular weight can be suitable for dispersing short fibers, while a copolymer having a high molecular weight can be suitable for dispersing long fibers.

[0060] A carbon fiber dispersion according to another aspect of the present application is produced by the method for producing a carbon fiber dispersion according to the present application, and may have a pH of 2 or more and 12 or less, and a viscosity of 10 cp or more and 200 cp or less.

[0061] A method for producing carbon paper according to yet another aspect of the present application may include a third step of molding the carbon fiber dispersion produced by the method for producing carbon fiber dispersion according to the present application, and a fourth step of drying the molded carbon fiber dispersion.

[0062] The third step is a step of forming the carbon fiber dispersion produced in the second step into a paper-like form by a wet process. For example, the carbon fiber dispersion can be formed into a paper-like form using a wet-laid nonwoven fabric manufacturing machine, a hand-made machine, etc.

[0063] The final carbon paper can then be produced by drying in the fourth step.

[0064] According to yet another aspect of the present application, there is provided carbon paper, which is produced by the method for producing carbon paper according to the present application and has a tensile strength of 25 kgf / cm 2 It may be more than that.

[0065] For example, the tensile strength of the carbon paper is 25 kgf / cm 2 Above, 30kgf / cm 2 Over 40kgf / cm 2 It may be more than that.

[0066] On the other hand, the carbon paper has a basis weight of 16 g / m 2 Alternatively, the thickness may be manufactured to be 120 to 150 μm, and the uniformity (dispersibility) measured by a 2D love formation sensor device may be 320 or less.

[0067] For example, the uniformity (dispersibility) of the carbon paper may be 320 or less, 310 or less, 300 or less, or 290 or less.

[0068] The present application will be described in more detail below using examples, but the present application is not limited thereto.

[0069] Production Example 1. Production of polymer Acrylic acid monomer (AA), acrylamide monomer (AM) and water were placed in a three-neck flask reactor, which was then equipped with a thermometer, purged with nitrogen and heated to 70°C.

[0070] The weight ratio of acrylic acid monomer (AA)+acrylamide monomer (AM) to water (weight of acrylic acid monomer (AA)+acrylamide monomer (AM):weight of water) was 2:8.

[0071] Next, ammonium persulfate (APS) was dissolved in water and then added dropwise for 30 minutes (0.1 parts by weight of APS was used per 100 parts by weight of the total content of acrylic acid monomer (AA), acrylamide monomer (AM) and water).

[0072] After the completion of the dropping, the mixture was kept at 70° C. for 7 hours, cooled, and then adjusted to pH 7.0 with NaOH to produce a polymer with a solid content of 25% and a weight average molecular weight of 100,000 g / mol.

[0073] Based on the total content of the polymer being 100 mol%, the mol% ratio of acrylic acid monomer (AA) to acrylamide monomer (AM) (mol% of acrylic acid monomer (AA):mol% of acrylamide monomer (AM)) was adjusted to 70:30 (D1), 30:70 (D2), 100:0 (D3), and 0:100 (D4) to prepare four polymers.

[0074] Production Example 2. Production of carbon fiber dispersion Based on a total content of 500 g, carbon fiber (Zolteck), polyvinyl alcohol (PVA) fiber (VPB-101, Kurary), and a non-ionic surfactant-based wetting agent (HPW-500, Hansol) were adjusted in their contents as shown in Table 1 below, and mixed with the remaining solvent (water), and then a pulper was applied to perform a pre-wetting step (a step of preparing a solution containing hydrophilized carbon fiber) at 1,000 rpm.

[0075] Thereafter, the solution containing the hydrophilized carbon fiber that had undergone the prewetting step was added to a polymer solution in which 2,000 g of a solvent (water) and the polymer (dispersant) prepared in Preparation Example 1 were dissolved, and the solution was stirred at a low speed of 300 rpm or less using an impeller that generates minimal vortex formation to prepare a carbon fiber dispersion.

[0076] The average lengths of the carbon fibers used were 6, 12, and 20 mm, respectively, as shown in Table 1 below.

[0077] In Examples 1 to 3 and Comparative Example 6, polymer D1 produced by the above-mentioned Production Example 1 was used as a dispersant, in Example 4, polymer D2 produced by the above-mentioned Production Example 1 was used as a dispersant, in Comparative Example 1, polymer D3 produced by the above-mentioned Production Example 1 was used as a dispersant, and in Comparative Example 2, polymer D4 produced by the above-mentioned Production Example 1 was used as a dispersant, and a carbon fiber dispersion was produced by Production Example 2.

[0078] On the other hand, in Comparative Examples 3 to 5, carbon fiber dispersions were produced according to Production Example 2 using CMC (carboxymethyl cellulose, Duksan Science, Mw 21,000 to 500,000) as a dispersant.

[0079] [Table 1]

[0080] As shown in FIG. 1 for the carbon fiber dispersions of Examples 1 to 4 and Comparative Examples 1 to 6, the dispersion speed was measured by measuring the time until rope-like aggregated carbon fibers were no longer visible to the naked eye.

[0081] In addition, after dispersion of the carbon fiber dispersions of Examples 1 to 4 and Comparative Examples 1 to 6, the dispersions were left to stand for 2 hours, and then the dispersion stability was evaluated by visually observing whether re-aggregation or sedimentation of the carbon fibers occurred.

[0082] The measured dispersion speed and dispersion stability of the carbon fiber dispersion are shown in Table 2 below.

[0083] [Table 2]

[0084] In the case of the carbon fiber dispersions of Examples 1 to 4, in which a copolymer of acrylic acid monomer (AA) and acrylamide monomer (AM) was used as a dispersant, it was confirmed that the dispersion speed of the dispersion was higher (the time required for dispersion was shorter) and the dispersion stability was improved, compared to the carbon fiber dispersions of Comparative Examples 1 and 2, in which a homopolymer in which acrylic acid monomer (AA) or acrylamide monomer (AM) was polymerized alone was used as a dispersant.

[0085] Furthermore, it was confirmed that the carbon fiber dispersions of Examples 1 to 4 had a higher dispersion rate (shorter time required for dispersion) and improved dispersion stability compared to the carbon fiber dispersions of Comparative Examples 3 to 5 in which CMC was used as a dispersant.

[0086] In particular, high dispersion stability was confirmed for the carbon fiber dispersions of Examples 2 to 4, which contained carbon fibers having relatively long average lengths of 12 mm and 20 mm.

[0087] In contrast, in Comparative Examples 1, 2 and 5, which were identical to Example 2 except that a homopolymer or CMC was used as a dispersant, it was not easy to disperse carbon fibers having an average length of 12 mm, and the dispersion stability was also very poor.

[0088] The carbon fiber dispersion of Comparative Example 6, in which the same polymer as in Examples 1 to 3 was used as a dispersant but which did not contain a wetting agent (i.e., did not undergo a prewetting step), did not easily disperse the carbon fibers, and the dispersion stability of the carbon fibers was also very poor.

[0089] That is, it was found that the prewetting step significantly affects the dispersion and dispersion stability of the carbon fibers in the carbon fiber dispersion.

[0090] Manufacturing Example 3: Manufacturing of Carbon Paper 25×25cm 2 The carbon fiber dispersions of Examples 1 to 4 and Comparative Examples 1 to 6 were made into paper using a hand sheet, and the paper was dried in a hot air drying oven at 120° C. for 30 minutes to produce carbon paper.

[0091] The carbon fiber dispersions of Examples 1 to 4 and Comparative Examples 1 to 6 were used to measure the dispersibility and tensile strength of the carbon paper produced in Production Example 3.

[0092] The dispersibility (uniformity) of the carbon paper was measured using Production Example 3 with a basis weight of 16 g / m 2 The dispersibility of carbon paper with a thickness of 120 to 150 μm was measured using a 2D lab formation sensor device manufactured by Techpap SAS (France).

[0093] The dispersibility of carbon paper can be evaluated based on the number and distribution of flocs measured by a 2D lab formation sensor device, and the lower the measured value, the better the dispersibility.

[0094] The tensile strength of the carbon paper was measured using a Shimadzu AGS-X 10N-10KN device at a speed of 2 m / min.

[0095] As shown in Figure 2, in the case of carbon paper produced using the carbon fiber dispersions of Examples 1 to 4, due to the excellent dispersibility of the dispersions of Examples 1 to 4, the measurement values ​​measured by a 2D lab formation sensor device were equivalent to 200 to 300, and it was measured that the carbon fibers were uniformly dispersed within the carbon paper.

[0096] In contrast, in the case of carbon paper produced using the dispersions of Comparative Examples 1 to 6, the measurement values ​​measured by the 2D lab formation sensor exceeded 320, confirming that the carbon fibers were not uniformly dispersed within the carbon paper.

[0097] The measured dispersibility and tensile strength of the carbon paper are shown in Table 3 below.

[0098] [Table 3]

[0099] In the case of carbon paper manufactured using the carbon fiber dispersions of Examples 1 to 4, the measurement values ​​measured by the 2D lab formation sensor device gradually increased as the length of the carbon fibers increased, but the measurement values ​​were below 300, indicating excellent dispersibility.

[0100] In contrast, in the case of carbon paper produced using the carbon fiber dispersions of Comparative Examples 1 to 6, it was confirmed that as the length of the carbon fibers increased, the measurement values ​​measured by the 2D lab formation sensor device rapidly increased, indicating that the dispersibility was significantly reduced.

[0101] In addition, it was confirmed that the carbon papers produced using the dispersions of Examples 1 to 4 had significantly improved tensile strength due to their excellent dispersibility compared to the carbon papers produced using the dispersions of Comparative Examples 1 to 6.

[0102] In particular, in the case of the carbon papers produced using the dispersions of Examples 1 to 3, it was confirmed that the tensile strength improved as the length of the carbon fibers increased.

[0103] In other words, it was confirmed that the copolymer of acrylic acid monomer (AA) and acrylamide monomer (AM) of the present invention can be used as an effective dispersant for carbon fibers having a relatively long average length of 12 mm or 20 mm.

[0104] It has been confirmed that the carbon fiber dispersion of the present invention has superior dispersion properties compared to existing carbon fiber dispersions, and therefore the properties of carbon paper can be improved by using the carbon fiber dispersion of the present invention.

[0105] The scope of the present invention is indicated by the claims set forth below rather than by the above detailed description, and all modifications and variations that fall within the meaning and scope of the claims and their equivalent concepts should be interpreted as being included in the scope of the present invention.

Claims

1. A first step of preparing a solution containing hydrophilized carbon fibers by adding carbon fibers, a wetting agent, and a binder to a solvent and stirring the mixture; A second step of dispersing the hydrophilized carbon fibers by adding a copolymer solution to the solution containing the hydrophilized carbon fibers, The average length of the carbon fibers is 5 mm or more, The copolymer is An acrylic acid monomer unit, Acrylamide monomer units, Including, a molar ratio of the acrylic acid-based monomer units to the acrylamide-based monomer units (mol % of the acrylic acid-based monomer units:mol % of the acrylamide-based monomer units) is 10:90 to 90:10, based on 100 mol % of the total content of the copolymer; Based on the total content of the carbon fiber dispersion liquid being 100% by weight, The copolymer is present in an amount of 0.1% by weight or more and 10% by weight or less, The carbon fiber is 0.01% by weight or more and 10% by weight or less, The binder is 0.001% by weight or more and 5% by weight or less, include, A method for producing carbon fiber dispersion.

2. In the first step, the mixture is stirred by applying shear force at a speed of 500 to 2,000 rpm; The method for producing the carbon fiber dispersion according to claim 1 .

3. In the second step, stirring is performed at a speed of 1,000 rpm or less. The method for producing the carbon fiber dispersion according to claim 1 .

4. The wetting agent is a cationic surfactant, an anionic surfactant, a nonionic surfactant, or a combination thereof; The method for producing the carbon fiber dispersion according to claim 1 .

5. The monomer polymerized as the acrylic acid-based monomer unit of the copolymer is acrylic acid, methacrylic acid, itaconic acid, 2-acrylamido-2-methylpropane sulfonic acid, maleic acid, or a combination thereof; The monomer polymerized as the acrylamide monomer unit of the copolymer is acrylamide, methacrylamide, or a combination thereof. The method for producing the carbon fiber dispersion according to claim 1 .

6. The copolymer has a pH of 5 or more and 10 or less, The viscosity is 100 cp or more and 20,000 cp or less. The method for producing the carbon fiber dispersion according to claim 1 .

7. The carbon fiber dispersion, The pH is 2 or more and 12 or less, The viscosity is 10 cp or more and 200 cp or less. The method for producing the carbon fiber dispersion liquid according to any one of claims 1 to 6.

8. A third step of molding the carbon fiber dispersion produced by the production method according to any one of claims 1 to 6; A fourth step of drying the formed carbon fiber dispersion. How carbon paper is manufactured.

Citation Information

Patent Citations

  • Method for impregnating porous sheet-like matter comprising carbon fiber with liquid having conductive solid dispersed therein

    JP2018159164A

  • Dispersant, carbon fiber web comprising the same, and carbon-fiber reinforced composite material composition

    KR1020180130840A

  • Planar heating paper using carbon fiber dispersion technology and Its manufacturing method

    KR1020220055337A

  • Aqueous dispersion of carbon microfibers, process for producing the aqueous dispersion, and article produced using same

    WO2010041750A1